2021
DOI: 10.3389/fendo.2021.699732
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Obesity as Risk Factors for Bladder Cancer Prognosis: A Systematic Review and Meta-Analysis

Abstract: BackgroundUrinary bladder carcinoma is common in developed settings, and prognosis may be impacted by lifestyle factors such as excess body weight and diabetes mellitus. The present meta-analysis aimed to systematically collate and analyze evidence on the impact of diabetes and excess BMI on bladder cancer outcomes.MethodsPubMed, Scopus, and Google Scholar databases were screened for relevant studies that examined the association between bladder cancer outcomes and diabetes and/or excess body weight. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Furthermore, BMI and multifocality were also independent predictive factors for worse outcomes in patients with pure CIS. BMI was investigated in many studies [32]and in the most recent metaanalysis was demonstrated that obese individuals were at higher risk for disease progression (HR 1.88, 95% CI: 1.41, 2.50, n=3) and recurrence (HR 1.60, 95% CI: 1.06, 2.40, n=7) compared to normal BMI patients [33]. Multifocality is a well known predictive factor for NMIBC [34], and its role is even more important in case of CIS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BMI and multifocality were also independent predictive factors for worse outcomes in patients with pure CIS. BMI was investigated in many studies [32]and in the most recent metaanalysis was demonstrated that obese individuals were at higher risk for disease progression (HR 1.88, 95% CI: 1.41, 2.50, n=3) and recurrence (HR 1.60, 95% CI: 1.06, 2.40, n=7) compared to normal BMI patients [33]. Multifocality is a well known predictive factor for NMIBC [34], and its role is even more important in case of CIS.…”
Section: Discussionmentioning
confidence: 99%
“…These pathologies can be interconnected. As mentioned above, diabetes mellitus is a risk factor for bladder cancer prognosis [ 64 ], and urinary incontinence is a common complication of bladder cancer [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes causes bladder remodeling leading to uropathy in a mulitfactorial way, with neurogenic and myogenic detrusor overactivity and changes in transmitter regulation leading to a hyper-excitability of the detrusor [ 63 ]. DM is also a risk factor for bladder cancer prognosis and outcome [ 64 ]. Diabetic cystopathy (urinary disturbances) is one of the most common complications of diabetes mellitus [ 65 ].…”
Section: Rac1 In Non-cancerous Bladder Pathologiesmentioning
confidence: 99%
“…Smoking is the most common modifiable cause of bladder cancer, and the prevalence among Aboriginal and Torres Strait Islander people is almost three times the general Australian population (43% vs 15%) 11 12. Chronic diseases, such as diabetes, have also been associated with increased prevalence and poorer prognosis of bladder cancer 13 14. The prevalence of diabetes among Aboriginal and Torres Strait Islander people in Australia is almost three times the general population (12.6% vs 4.3%) 15.…”
Section: Introductionmentioning
confidence: 99%